HUBUNGAN ANTARA KECEPATAN PEMBERKASAN REKAM MEDIS ELEKTRONIK RAWAT JALAN DAN KETEPATAN WAKTU PENGUMPULAN BERKAS JAMINAN KESEHATAN NASIONAL (JKN) DI KLINIK INTERNE RS BETHESDA - Amelia Handayani Burhan; Ibnu Mardiyoko (Politeknik Kesehatan Bhakti Setya Indonesia, 2018)
Medical records as one of the conditions for submitting claims for National Health Insurance (JKN), where JKN file collection has a time limit. Therefore, the speed needed to manage medical record files, one with electronic archiving. The purpose of this study was to determine the relationship between the speed of filing electronic medical records on the timeliness of JKN outpatient file collection at the Interne Clinic of Bethesda Hospital, Yogyakarta. This research method uses analytic observational studies. The population of this study was 536 JKN Interne Clinic files, with a sample of 284 electronic medical record files. Furthermore, the data was processed statistically using Chi-Square and simple logistic regression. The results showed that there was a relationship between the speed of electronic filing and the timeliness of JKN file submission. The relationship is the effect of the speed of filing electronic medical records on the timeliness of JKN file collection with the risk of small inaccuracies (PR <1).